Replacing Death with Life? The Rise of LWOP in the Context of Abolitionist Campaigns in the United States - Miao, Michelle (2020)
On the basis of fifty-four elite interviews[1] with legislators, judges, attorneys, and civil society advocates as well as a state-by-state data survey, this Article examines the complex linkage between the two major penal trends in American society during the past decades: a declining use of capital punishment across the United States and a growing population of prisoners serving “life without the possibility of parole” or “LWOP” sentences. The main contribution of the research is threefold. First, the research proposes to redefine the boundary between life and death in relation to penal discourses regarding the death penalty and LWOP. LWOP is a chronic and latent form of ultimate punishment that strips life of its most valuable existential character. Second, the findings explore the connection between the rise of LWOP and the nationwide campaign against capital punishment. It explains that the abolition campaign normalized and accentuated LWOP as a symbolic substitute for the death penalty. The research reveals the thorny ethical and moral dilemmas facing anti-death penalty activists at the forefront of the abolitionist movement. Third, this Article demonstrates that the judicial use of LWOP and capital punishment at the state level does not support the claim that the expansion of LWOP caused a decline in capital punishment. In sum, LWOP has not merely been employed as a penal punishment for the United States’ most incorrigible criminal offenders—it has also been used as a strategic instrument to reshape American penal politics. [1] Elite interviewing or elite interview refers to a methodology to study elite members of society in superior positions in a given field or arena in society, be it business or politics. The field of study in this project involves criminal justice and law. See generally Victor Jupp, Elite Interviewing, in The SAGE Dictionary of Social Research Methods (2006); Jeffrey M. Berry, Validity and Reliability Issues In Elite Interviewing, 35 PS: Pol. Sci. & Pol. 679 (2002); David Richards, Elite Interviewing: Approaches and Pitfalls, 16 Pol. 199 (1996)